2013
DOI: 10.1073/pnas.1209507110
|View full text |Cite
|
Sign up to set email alerts
|

Role of poly(ADP-ribose) polymerase-1 in the removal of UV-induced DNA lesions by nucleotide excision repair

Abstract: Among the earliest responses of mammalian cells to DNA damage is catalytic activation of a nuclear enzyme poly(ADP-ribose) polymerase-1 (PARP-1). Activated PARP-1 forms the polymers of ADPribose (pADPr or PAR) that posttranslationally modify its target proteins, such as PARP-1 and DNA repair-related proteins. Although this metabolism is known to be implicated in other repair pathways, here we show its role in the versatile nucleotide excision repair pathway (NER) that removes a variety of DNA damages including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
160
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(175 citation statements)
references
References 22 publications
11
160
3
1
Order By: Relevance
“…The N-terminal DNA binding domain of PARP-1 that is known to be recruited to DNA strand breaks 20 was also recruited to UV-lesions without strand breaks, indicating more general property of this domain of PARP-1 to bind to different types of DNA damages. Our model is also consistent with previously reported interactions of DDB2 and PARP-1 at the UV-lesion site 5,7 . We have earlier shown that PARP-1 and DDB2 co-immunoprecipitate at the UV-damaged chromatin in the presence of ethidium bromide, indicating their direct interaction on the same DNA strand 7 .…”
Section: No Effect Of Parp-1 and Ddb2 Binding On Cpd-photolyase Mediasupporting
confidence: 93%
See 4 more Smart Citations
“…The N-terminal DNA binding domain of PARP-1 that is known to be recruited to DNA strand breaks 20 was also recruited to UV-lesions without strand breaks, indicating more general property of this domain of PARP-1 to bind to different types of DNA damages. Our model is also consistent with previously reported interactions of DDB2 and PARP-1 at the UV-lesion site 5,7 . We have earlier shown that PARP-1 and DDB2 co-immunoprecipitate at the UV-damaged chromatin in the presence of ethidium bromide, indicating their direct interaction on the same DNA strand 7 .…”
Section: No Effect Of Parp-1 and Ddb2 Binding On Cpd-photolyase Mediasupporting
confidence: 93%
“…We have earlier shown that PARP-1 binds to UV-damaged large oligonucleotide in vitro or to chromatin fragments containing T-T lesions in vivo 11 . We also showed that PARP-1 and DDB2 associate with each other on the chromatin of UV-irradiated cells and that DDB2 stimulates catalytic activity of PARP-1 in the presence of UV-damaged DNA 7 . However, these assays lack the nucleotide level resolution to reveal whether PARP-1 was bound directly to the UV-damaged bases or to any other base in those long pieces of DNA and whether PARP-1 and DDB2 have sufficient space to co-exist around UV-induced DNA lesion.…”
mentioning
confidence: 59%
See 3 more Smart Citations